Uso de marcadores parasitológicos e imunológicos na seleção de ovelhas resistentes às parasitoses gastrintestinais - Rosalinski-Moraes, Fernanda; Sotomaior, Cristina Santos; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Thomaz-Soccol, Vanete (My University, 2011)
This work was conducted to verity the possibility to identify adult sheep that are resistant to parasites by using a parasitological marker (direct), immunological markers (indirect) or by the association of both types of markers. Twenty ewes were sampled monthly for blood and faeces, from July of 1998 to June of 1999. Faecal egg counts (FEC) was chosen as parasitological marker. The number of peripheral eosinophils, IgE and IgG anti-Haemonchus contortus were used as immunological markers. Sheep could be classified as resistant or susceptible by FEC. Both peripheral eosinophils and specific IgE data could be joined to FEC in order to identify resistant or susceptible animals. The number of peripheral eosinophils was the only immunological maker that was able to classify high and low FEC ewes in two different groups.
Usage of parasitological and immunological markers for the selection of ewes resistant to gastrointestinal parasites
Keywords: Eosinophils; Immunoglobulin E; Immunoglobulin G; Resistance to nematodes